Significance of miR-196b in tumor-related epilepsy of patients with gliomas. - Gan You; Wei Yan; Wei Zhang; Yongzhi Wang; Zhaoshi Bao; Shouwei Li; Shaowu Li; Guilin Li; Yijun Song; Chunsheng Kang; Tao Jiang (PLoS ONE, 2012)
OBJECTIVES: Seizure is a common presenting symptom of primary brain tumors. There are no published studies regarding the roles of MicroRNA (miRNA) in tumor-related epilepsy. The authors set out to correlate miR-196b expression in low-grade glioma patients with pre-operative seizures and post-operative seizure control. METHODS: Twenty-three patients with WHO grade II astrocytomas and 83 similar patients for independent validation were included. Follow-up visits regarding seizure prognosis were scheduled at 6 months. MiRNA profiling was used to identify differentially expressed miRNAs. The most important miRNA was determined by quantitative reverse-transcriptase polymerase chain reaction (q-PCR) in the validation cohort. Gene ontology (GO) analysis and whole genome mRNA profiling was performed to investigate the underlying biological processes. RESULTS: Array results showed that 30 miRNAs were overexpressed and 10 miRNAs were underexpressed (with more than 2 fold change) in patients with pre-operative seizures. MiR-196b was validated in the independent validation cohort. Patients with good seizure prognosis exhibited low levels of miR-196b expression compared with those who had poor seizure prognosis in the group without pre-operative seizures. Biological processes that relate to transcription and cell cycles were over-represented in the miR-196b-associated gene expression signature. MiR-196b-associated gene expression profiling was characterized by enrichment of genes usually involved in cell proliferation. CONCLUSIONS: We have provided the first evidence that expression of miR-196b was associated with the occurrence of pre-operative seizures in low-grade gliomas, and may predict seizure prognosis in patients without pre-operative seizures. Targeted treatments that decrease endogenous levels of miR-196b might represent novel therapeutic strategies.